EFFECT OF SOCIAL ECONOMIC FACTORS ON INCOME CORN FARMERS - Khairunnisa Rangkuti; Muhammad Thamrin; Rui Andriano (AGRIUM: Jurnal Ilmu Pertanian, 2016)
This studyaimed to determine theeffect ofsocioeconomic factorson theincome of farmerscornand to know cornfarming efficiencyin Lau Tawar Village, District Tanah Pinem, Dairi. Sampling method using simple random sampling methodis to takea simple random. Data analysis method usedis multiple linearregression analysis. The results of thestudy basedon the results of multiple linearregression analysis are obviousor significantin fluence between thelandand laborof thefarm income cornand there is norealin fluen ceornot significan tbetween thecapital, farming experienceand the number of dependents of the cornfarm income. Andbased on the analysis of O/Iratio, maize farmingin the study areahas beenefficient. Keywords: socio-economic factors, efficiency, revenue, corn